Appropriate scales and data to manage seabird-fishery interactions: Comment on Torres et al. (2013) - Croxall, John (2013)
Torres et al. (2013; Mar Ecol Prog Ser 473:275-289) use fine-scale data on tracked locations of one species of albatross and fishing vessels to make a variety of assertions on interactions between them, especially in relation to risk of bycatch. Some of these assertions are incorrect, and we seek to clarify the issues and perspectives involved. We argue that while a fine-scale approach can provide interesting insights into foraging behaviour, large-scale risk analysis is needed because management measures (e.g. for bycatch mitigation) need to operate across all vessels in a fishery and across all seabird species at risk from the fishing operation. In addition, an estimate of 10% time spent in close proximity to vessels cannot be used to infer low bycatch risk alone: such an inference would need comparison to bycatch rate data. The analysis also does not take into account a number of factors known to affect the nature and duration of the association of albatrosses with fishing vessels, which limits the conclusions that can be drawn. However, fine-scale studies can provide important insight into factors affecting individual bycatch events, and studies at fine and broad scales will be complementary.